Da escola negada ao trabalho necessário: um olhar sobre a educação de jovens e adultos no bairro de bodocongó em Campina Grande-PB - Almeida, Juliana Nobrega de (2010)
This paper presents a theoretical challenge to understand how to establish the current relationship between school and work in the neighborhood of Bodocongó in Campina Grande-PB, through the daily life of students workers to from the State School Professor EJA Itan Pereira. This research develops a neighborhood that was considered for decades as an industrial district, bound by old factories and tanneries which appeared in this space mainly in the 1940s to exist until the 1990s. We seek to know the historical formation of Bodocongó because this neighborhood is presented as space: home, school, work for many students the workers of the EJA searched the school. We resume some of the main characteristics of the type of education that meets students those workers who return to the school: the EJA. We believe that students the workers of the EJA are mostly sons of former factory workers and are inserted in the world of informal work, causing the sale of its workforce to ensure their reproduction and their families. Thus the struggles for education is denied to be the main action that motivates students the workers of the EJA to return to school, searching through the school, not only have access to knowledge, but also the city. Today the students the workers of the EJA in Bodocongó relate differently with the world of work by comparing the current working class in which their parents and grandparents were a part, because the productive restructuring of the industrial sector caused an impact on inclusion of formal work for the current generation of young and adult workers with the bankruptcy of its factories and tanneries. For that education should serve as foundation to provide students the workers conditions to overcome the barriers of social exclusion, informality, underemployment and unemployment, because that way we can understand social work as a whole, considering the dialectical process that unifies the environmental and socio-spatial dimensions.